Removal of chromium (VI) from aqueous solution using treated oil palm fibre - Mohamed Hasnain, Isa; Naimah, Ibrahim; Hamidi, Abdul Aziz; Mohd. Nordin, Adlan; Nor Habsah, Md. Sabiani; Ali Akbar Lorestani, Zinatizadeh; Shamsul Rahman, Mohamed Kutty (Elsevier B.V, 2009)
Link to publisher's homepage at http://www.elsevier.com/wps/find/journaldescription.cws_home/502691/description#description